Theology and Culture: Walisongo’s Strategy of Islamic Enculturation in Java - Muhammad Ibnu Aminim; Galuh Maria; Suhermanto Ja'far (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This study explores the theological and cultural dynamics of Islam in Java through the lens of Islamic enculturation as practiced by Walisongo, the nine saints who played a pivotal role in the Islamization of the region. Using a socio-theological framework, this study examines how Islamic teachings were not merely introduced but were harmonized with pre-existing Javanese cultural forms. The Walisongo adopted a syncretic and accommodative strategy, utilizing local traditions, such as wayang, gamelan, and traditional poetry, as mediums for daʿwah, thereby fostering a peaceful and holistic process of religious transformation in Indonesia. Their method was not confrontational but integrative, respecting local wisdom while gradually embedding Islamic values. This strategic adaptation ensured a more profound and lasting acceptance of Islam, shaping Javanese religiosity into a unique cultural expression that blended spirituality with aesthetic and communal dimensions. This study highlights that Walisongo’s approach to daʿwah exemplifies a model of inculturation that goes beyond mere tolerance; it embodies a theological vision of harmony between divine revelation and cultural identity. This article contributes to the contemporary discourse on religion and culture by demonstrating how Islamic theology can inform intercultural dialogue and religious transmission in pluralistic societies.